Country Partnership Framework for the Republic of Seychelles for the Period of FY18-FY23 - World Bank Group (World Bank, Washington, DC, 2018)
This Country Partnership Framework (CPF) for Seychelles covers the period FY18-FY23. Seychelles has achieved impressive gains in prosperity and stability in the past decade since confronting a major economic crisis in 2008. The government responded to the crisis with a wide-ranging reform program supported by generous debt relief that focused on liberalization of the trade and exchange regimes, significant and sustained fiscal consolidation underpinned by reductions in public employment and subsidies, and a reduction in the state’s role in the economy to boost private sector development. Along with the International Monetary Fund (IMF), the World Bank Group (WBG) supported Seychelles in managing the crisis and regaining stability. The CPF is grounded in the findings of a WBG Systematic Country Diagnostic1 (SCD) that was finalized in July 2017. The SCD assesses the remaining institutional constraints and priorities to bolster inclusion in a sustainable manner. The SCD shows that progress during the last decade has mostly benefitted the more skilled population, and that enhancing inclusion requires greater attention to the quality of education and social assistance The CPF is consistent with the principles for international Bank for Reconstruction and Development (IBRD) engagement in countries above the Graduation Discussion Income (GDI) and the Forward Look on small states. The CPF puts forward a flexible approach for the WBG’s program that is appropriate for addressing key institutional gaps and buttressing the resilience of the economy. The CPF focuses on strengthening institutions to foster inclusive and sustainable prosperity through a highly selective framework centered on two focus areas. The first focus area, Sustainable Growth for Shared Prosperity, seeks the retooling of tourism and fisheries, the core sectors of the economy, to open opportunities for local business to generate higher value-added and better paying employment opportunities, especially, among the bottom 40 percent of the income distribution. The second focus area, Fostering Inclusion and Public Sector Performance, supports the government’s efforts to reorient its significant investment in social assistance towards investment in human capital, especially the bottom 40 percent